Hubungan Iklim Kelas Dengan Motivasi Belajar Di SMA Global Prima Medan - Selline Herty Lauren; Yosevin Yemima Siregar; Putri Sherina Arzilla; Haposan Lumbantoruan; Beby Astri Tarigan (Jayapangus Press, 2026)
This study addresses the issue of low learning motivation among students, which is presumed to be associated with classroom climate. An unconducive classroom environment may hinder students’ engagement, participation, and enthusiasm in learning. This study aims to examine the relationship between classroom climate and students’ learning motivation at SMA Global Prima Medan. A quantitative correlational design was employed with a sample of 140 students. Data were analyzed using Pearson’s Product Moment correlation with the assistance of SPSS 25.0. The results indicate that classroom climate is categorized as high, with an empirical standard deviation lower than the hypothetical standard deviation (11.196 < 14.5), suggesting relatively homogeneous student perceptions. Furthermore, a significant positive relationship was found between classroom climate and learning motivation. This finding indicates that a more supportive classroom climate is associated with higher levels of student motivation. Most students were found to have moderate levels of learning motivation and classroom climate perception, although a small proportion fell into the low category. In conclusion, classroom climate plays an important role in shaping students’ learning motivation. This study highlights the need for teachers and schools to foster a conducive and supportive classroom environment to enhance student engagement and motivation.